1994
DOI: 10.1007/bf00756764
|View full text |Cite
|
Sign up to set email alerts
|

Periodic fluctuations in proliferation of SV-40 transformed human skin fibroblast lines with prolonged lifespan

Abstract: A human fibroblastic cell line transformed by the SV40-T antigen sequence and continuously cultured for 7 months displayed large periodic variations in cell proliferation. This contrasted with other characteristics of this cell line that remained constant: mosaic cell shape, absence of cell contact inhibition, and predominance of a hypodiploid population. Similar fluctuations in proliferative capacity were also found during the long-term growth of a transformed but nonimmortalized human fibroblastic line prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Proliferation curves of both normal and transformed human embryonic fibroblasts, and of Fao hepatoma cells, maintained in longterm culture, showed regular rises and falls of cell proliferation rate. These observations are similar to those previously reported for SV40T-transformed human skin fibroblasts (34). These waves of cell proliferation were about 3 to 4 wk long, with variations depending on the cell line, for cells passaged about every week.…”
Section: Growth Of Rat Hepatoma Fao Cellssupporting
confidence: 88%
See 1 more Smart Citation
“…Proliferation curves of both normal and transformed human embryonic fibroblasts, and of Fao hepatoma cells, maintained in longterm culture, showed regular rises and falls of cell proliferation rate. These observations are similar to those previously reported for SV40T-transformed human skin fibroblasts (34). These waves of cell proliferation were about 3 to 4 wk long, with variations depending on the cell line, for cells passaged about every week.…”
Section: Growth Of Rat Hepatoma Fao Cellssupporting
confidence: 88%
“…However, we previously showed that the rate of proliferation of such cell lines, whether long established like hamster Nil cells, or human fibroblasts with life span extended by recent SV40-T transformation, is not constant. The proliferation pattern displays regular rises and fails (34). Here, we report the population dynamics of three other long-lived cell lines: the rat hepatoma Fao cell line and one embryonic human fibroblast cell line and its ~Equal contributors to these studies.…”
Section: Introductionmentioning
confidence: 95%
“…1 and 2 with the highest deuterium content D/H 500.000 ppm and D/H 100.000 ppm. Since the PDT serves as one of the main cell proliferation activity indicators [ 20 ], its increase in the ADSCs population indicates cell cycle slowdown and, as a consequence, a decrease in the cell proliferation rate at high deuterium levels in the growth medium.…”
Section: Resultsmentioning
confidence: 99%
“…SigmaScan Pro 5.0 Analysis Software (SPSS Inc., USA) was used to count cells on images. The proliferation rate of ASCs was estimated as the number of population doublings (PD), PD = log 2 N/No, where No and N—initial and final cell number …”
Section: Methodsmentioning
confidence: 99%